Direct estimation of maize leaf area index as influenced by organic and inorganic fertilizer rates in Guinea Savanna - Berdjour, A.; Dugje, I.; Rahman, N.A.; Odoom, D.A.; Kamara, A.; Ajala, S. (Canadian Center of Science and Education, 2020)
Leaf area index (LAI) plays an important role in radiation capture, crop growth and yield formation. However, there is limited quantitative data on the influence of poultry manure (PM) and NPK fertilizer rate (NPK) on LAI, as estimated directly. Using a split-plot design with three replications, a field experiment was conducted to determine the effects of three PM rate (0, 2 and 4 t/ha) as main plot and three NPK rate (0:0:0, 60:30:30 and 120:60:60 kg N P2O5 K2O/ha) as sub plot, on LAI and maize grain yield. The maize was planted at a density of 106,666 plants/ha; two rows on a ridge, one plant per stand at 75 × 25 cm. Linear regression was used to establish predictive equations among correlated variables and to describe the degree of associations. The application of PM in maize increased (p < 0.05) number of leaves/plant (NL) at 8 and 10 weeks after sowing maize (WASM). NL, leaf area constant at 6 and 10 WASM, leaf area (LA) and LAI were significantly affected by NPK. LAI correlated positively with NL, LA and grain yield. The coefficient of determination between actual and estimated LA was in the range of 0.85-0.97. The PM × NPK interaction was significant on maize grain yield. The results suggest that small-scale maize farmers faced with challenges in obtaining and transporting large quantities of poultry manure can use 2 t PM/ha with either 60:30:30 kg N P2O5 K2O/ha or 120:60:60 kg N P2O5 K2O/ha to increase grain yield of maize.